SOCIAL MEDIA: THE ‘FORM OF LIFE’ OF THE POST-MILLENNIAL GENERATION IN THE PHILIPPINES - Eugene Victoriano De Guzman (INTERNATIONAL JOURNAL OF HUMANITIES, PHILOSOPHY AND LANGUAGES (IJHPL), 2024)
Meaning and use is one of the most notable accounts of Ludwig Wittgenstein in his Philosophy of language. This idea paves a way to consider the form of life in determining and understanding the meaning of a words or language. In ordinary use of language, the meaning of a word is to be understood by knowing its use (see Hartnack 1962, 69). Thus, the meaning of a word is its use in the language-game. Social Media has become indispensable in quotidian existence of every individual in 21st century particular for the post-millennial generation. This occurrence generated to the fact that social media has become the form of life of them. A form of life that yielded new meaning to some words due the agreement of the linguistic community within the language-game. This work is dedicated to explain the misunderstanding occurrences between the past generation and post-millennial generation especially when using words in social media and their attitudes. Likewise, this paper will explicate the meaning-use phenomenon on language in the social media platforms that everyone is conventionally encountering at.